2007
DOI: 10.1016/j.ygeno.2007.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A humanized IKBKAP transgenic mouse models a tissue-specific human splicing defect

Abstract: Familial dysautonomia (FD) is a severe hereditary sensory and autonomic neuropathy, and all patients with FD have a splice mutation in the IKBKAP gene. The FD splice mutation results in variable, tissue-specific skipping of exon 20 in IKBKAP mRNA, which leads to reduced IKAP protein levels. The development of therapies for FD will require suitable mouse models for preclinical studies. In this study, we report the generation and characterization of a mouse model carrying the complete human IKBKAP locus with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 25 publications
1
81
0
Order By: Relevance
“…The day of vaginal-plug discovery was designated 0.5 dpc. The transgenic mouse lines that carry human IKBKAP transgenes were generated as previously reported (23). The mice used for this study were housed in the animal facility of Massachusetts General Hospital (Boston, MA), provided with constant access to a standard diet of food and water, and maintained on a 12-hour light/dark cycle, and all experimental protocols were approved by the Subcommittee on Research Animal Care at the Massachusetts General Hospital.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The day of vaginal-plug discovery was designated 0.5 dpc. The transgenic mouse lines that carry human IKBKAP transgenes were generated as previously reported (23). The mice used for this study were housed in the animal facility of Massachusetts General Hospital (Boston, MA), provided with constant access to a standard diet of food and water, and maintained on a 12-hour light/dark cycle, and all experimental protocols were approved by the Subcommittee on Research Animal Care at the Massachusetts General Hospital.…”
Section: Animalsmentioning
confidence: 99%
“…Recently, we described the creation of transgenic mouse lines that carry the normal human IKBKAP gene and the FD IVS20ϩ6TϾC mutation. All of these lines are phenotypically normal, and the IVS20ϩ6TϾC transgenics missplice IKBKAP in a tissue-specific manner that mimics what is seen in FD patients (23). To test whether embryonic lethality caused by ablation of mouse Ikbkap could be rescued by human IKAP, we crossed two transgenic lines, one carrying the normal IKBKAP gene and one with the IVS20ϩ6TϾC mutation, with Ikbkap ϩ/Ϫ mice in order to introduce the human transgenes into the Ikbkap knockout mouse line.…”
Section: Fig 4 Appearance Of Ikbkapmentioning
confidence: 99%
“…There is no evidence that the mutant transcript yields IKAP protein, and therefore, FD can be considered as a partial loss of IKBKAP function disease. Interestingly, the extent of IKBKAP missplicing in FD patients shows considerable tissue-specific differences [32,40] that may underlie the tissue-specific clinical symptoms of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mice null for IKBKAP are developmentally arrested at midgastrulation resulting in early embryonic lethality [47]. The generation of bacterial artificial chromosome (BAC) transgenic mice carrying the human BAC with the FD disease-causing mutation has been used to model tissue-specific splicing of the IKBKAP gene [40]. However, introducing the human disease-specific BAC onto an IKBKAP-null mouse background leads to a complete rescue of embryonic lethality without any signs of disease in the resulting mouse [47].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a 3Ј-end-truncated mRNA transcript of IKBKAP is expressed at variable levels in different tissues together with full-length IKBKAP (Slaugenhaupt et al, 2001;Anderson et al, 2001). The pathogenic result of the IKBKAP splice mutation is a tissue-specific reduction of wild-type IKAP protein below a tolerable threshold in the sensory and autonomous nervous systems (Slaugenhaupt et al, 2001;Cuajungco et al, 2003;Hims et al, 2007). It is not known whether the truncated IKAP transcript resulting from the exon skipping is degraded or whether it is translated into a C-terminally truncated IKAP protein termed here as FD-IKAP.…”
mentioning
confidence: 99%